Healthcare worker exposure to Middle East respiratory syndrome coronavirus (MERS-CoV): Revision of screening strategies urgently needed - Amer, Hala (Int J Infect Dis, 2018)
OBJECTIVES: Middle East respiratory syndrome coronavirus (MERS-CoV) continues to cause frequent hospital outbreaks in Saudi Arabia, with emergency departments as the initial site of the spread of this virus. METHODS: The risk of transmission of MERS-CoV infection to healthcare workers (HCWs) was assessed in an outbreak in Riyadh. All HCWs with unprotected exposure to confirmed cases were tested after 24 h of exposure. Two negative results for MERS-CoV obtained 3 days apart and being free of any suggestive signs and symptoms were used to end the isolation of the HCWs and allow their return to duty. RESULTS: Overall 17 out of 879 HCWS with different levels of exposure tested positive for MERS-CoV. Of the 15 positive HCWS with adequate follow-up, 40% (6/15 HCWs) tested positive on the first sampling and 53% (8/15) tested positive on the second sampling. The time to negative results among the 15 positive HCWs ranged between 4 and 47 days (average 14.5 days) and the infected HCWs needed on average two samples for clearance. All positive HCWs were either asymptomatic or had mild disease. CONCLUSIONS: The data obtained in this study support the widespread testing of all close contacts of MERS-CoV cases, regardless of the significance of the contact or presence or absence of symptoms. In addition, urgent careful review of guidance regarding the return of asymptomatic MERS-CoV-positive HCWs under investigation to active duty is needed.